Hybrid Language: Proof Harmony of Arab-Nusantara Cultural Acculturation - Bukhori (International Journal of Science and Society, 2019)
This study aims to analyze the arabic-archipelago hybrid language. The factor of grammar changes that occur in the Arabic-Archipelago language is supported by (a) the Arabic-speaking community that has its own prestige - its nationality which refers to the descendants of the prophet Muhammad, so that it has a positive charisma among the Nusantara community which is a mostly Muslim population in the world; (b) a very close degree of intimacy in social relations at the start even as evidenced by their participation in the struggle for Indonesia's revival; (c) demographic factors with the establishment of Arab villages (other than Chinatown) during the Dutch colonial period. The development of Arabic used as a language of commerce and religion is not inferior when compared to English, which is currently a global language in the world. The social interaction of Arab descendants and indigenous communities is manifested in the development of a new culture (in this case, language) in a genealogical society.